PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP KERENTANAN SISTEM PADA PERDAGANGAN SAHAM BERBASIS AI - wildayanti wildayanti; Rehulina Rehulina (Jurnal Perspektif Hukum, 2025)
Artificial Intelligence (AI)-based stock trading is a technological innovation that has transformed the way investors interact with the capital market. Algorithmic and machine learning-based systems enable automated decision-making with high speed and accuracy. However, this development also presents new challenges in the form of cybersecurity risks, algorithmic bias, and the potential for market manipulation that have not been fully addressed by legal regulations in Indonesia. This study aims to analyze the forms of legal protection for investors regarding the vulnerabilities of AI-based stock trading systems and to evaluate the effectiveness of regulations implemented by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX). This study uses a normative juridical method with a statutory and conceptual approach, through an analysis of the Capital Market Law, the Consumer Protection Law, and OJK Regulations concerning electronic systems in the financial sector. The results show that although a basic legal framework for investor protection is in place, protection mechanisms against risks stemming from AI technology failures remain unspecified. Therefore, regulatory updates based on risk governance and an AI accountability framework are needed to create legal certainty and secure digital trading systems in the future.